Torsion of the gravid uterus: A rare cause of abdominal pain (Indian Journal of Case Reports, 2020)
Uterine torsion in pregnancy is a rare clinical entity with a non-specific clinical presentation. Here, we present a case of uterine torsion, which was diagnosed at laparotomy done for the lower segment cesarean section (LSCS) in a case of central placenta previa with the fetus in transverse lie. At 36.4 weeks period of gestation, the patient complained of severe left-sided abdominal pain which was not suggestive of labor. This abdominal pain was refractory to analgesics. Emergency LSCS was done which confirmed uterine torsion as well as anterior sacculation.